Bank ownership and efficiency in the aftermath of financial crises : evidence from Indonesia - Riyanto, Yohanes Eko (2014)
This paper examines the relationship between types of ownership of banks and their efficiency in the aftermath of a financial crisis using Greene's “true” panel data stochastic frontier model, which takes into account unobserved heterogeneity among banks. The Indonesian banking sector is analyzed using financial data of 144 banks operating in Indonesia over the period of 2000Q4–2005Q2. In the aftermath of the 1997 Asian financial crisis, the cost efficiency of all banks improves over time on average. However, there is some evidence that, as these banks improve their efficiency, state-owned banks are the least efficient banks while joint-venture and foreign-owned banks are the most efficient.